The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/jcm11205987
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Characteristics of Pediatric COVID-19 Population—A Bibliometric Analysis

Abstract: The literature on the COVID-19 landscape has rapidly expanded in the pandemic period. The current study undertakes a bibliometric analysis of research in the topic of the clinical and laboratory characteristics of pediatric COVID-19 cases. Our aim is to perform a comprehensive bibliometric review of current research trends and patterns of this research domain. Publications retrieved from the Web of Science Core Collection and VOSviewer were used for analysis and network visualization. We analyzed geographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
1
0
0
Order By: Relevance
“…Non COVID-19: 70%), and breathing difficulties occurring only in COVID-19-positive patients. Fever as a symptom of SARS-CoV-2 infection was reported with varying frequency in pediatric patients, ranging from 43.5% to 90.9% [7,14,[28][29][30][31][32][33][34]. The results obtained are similar to those reported by Alpcan et al [14], who identified fever as the most frequent symptom (61.3%) in patients infected with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 88%
“…Non COVID-19: 70%), and breathing difficulties occurring only in COVID-19-positive patients. Fever as a symptom of SARS-CoV-2 infection was reported with varying frequency in pediatric patients, ranging from 43.5% to 90.9% [7,14,[28][29][30][31][32][33][34]. The results obtained are similar to those reported by Alpcan et al [14], who identified fever as the most frequent symptom (61.3%) in patients infected with SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 88%
“…The process of study selection is described using a PRISMA flow diagram in Figure 1. The bibliometric analysis and visualizations were performed by using Visualization of Similarities viewer (VOSviewer) software (VanEck andWaltman, Center for Science and Technology Studies of Leiden University [4,5]), a tool that has been used in studies in various areas of research [6][7][8][9][10][11][12][13][14][15][16][17]. Bibliographic techniques, such as citation and co-citation analysis, bibliographic coupling and co-occurrence analysis, were used to create collaboration networks and text mining.…”
Section: Methodsmentioning
confidence: 99%
“…Co-cited journals are the phenomenon of two journals being cited in the same literature, reflecting the relevance of various journals and disciplines (20). The analysis of co-cited journals can be used to locate and categorize journals, determine their core or marginal position in the field, and evaluate the importance of academic journals (21). Among the top 15 cocited journals (Table 2), five journals had more than 2,500 cocitations, with Journal of Neuroscience (n = 10,018) being the most co-cited journal, followed by Experimental Neurology, Journal of Neuroinflammation, Journal of Neurotrauma, and Brain.…”
Section: Analysis Of Journals and Co-cited Journalsmentioning
confidence: 99%